Measurements and assessment of sound emitted by toys intended for children below 3 years old - GRYNKIEWICZ-BYLINA, Beata; RAKWIC, Bożena (Archives of Acoustics, 2015)
Toys emitting sounds are classified as significant sources of noise found in the children environment. Impulse and continuous noise emitted by toys, used in close to the child’s ear, acting directly on the organ of hearing, can lead to serious adverse health effects. This is especially true for children under the age of three, in which the state of the hearing organ determines their intellectual development. The current level of safety of sound emitting toys intended for children in this age group is insufficient This is confirmed by the reports from the control of market surveillance authorities. A new approach to the assessment of children’s exposure to noise generated by toys, included in EN 71-1:2011 + A2:2013 Standard, based on the permissible values applicable to the workplaces, requires further tests and verification. The paper presents the results of the research work and assesses the level of sound emitted by toys in the light of current standard requirements, carried out using the author’s methodology. Toys intended for children under the age of 3 years, commercialized on the European market by Polish manufacturers and importers were tested. The results of the tests allowed us to determine the impact of duration of the sound pressure level measurement on the final result.